LEARNING MANAGEMENT MODEL: IMAGES OF METHODS AND IMAGES IN IMPROVING EARLY CHILDREN'S LEARNING OUTCOMES - Qolbi, Miftahatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
At an early age, it is a top priority to stimulate all learning forms so children's development can develop optimally. This study aims to analyze and examine the management of the Picture And Picture Learning model in improving early childhood learning outcomes; learning management is carried out to assist teachers in implementing learning so that early childhood learning outcomes are further enhanced. Researchers used a qualitative approach to the type of case study. This research was conducted at the Alhasyimi Kalidandan PAUD institution, Probolinggo. Sources of informants were obtained from school principals, teachers and employees. The study results show that the Alhasyimi Kalidandan Pakuniran Probolinggo PAUD school has used the picture-and-picture learning model to improve the learning outcomes of its students. The implementation of picture and picture learning is carried out in several stages. The first stage is preliminary design, the second stage is the picture and picture model implementation, and the third stage is evaluation. Performance achieved by using the picture and picture method, students are more interested and enthusiastic about participating in learning to increase children's learning outcomes.